Indigenous Making and Sharing: Claywork in an Indigenous STEAM Program. Issue 1 (2nd January 2018) - Barajas-López, Filiberto; Bang, Megan
ABSTRACT: In this article we expand on ideas of making and maker spaces to develop Indigenous making and sharing. We draw from an ArtScience participatory design project that involved Indigenous youth, families, community artists, and scientists in a summer Indigenous STEAM program designed to cultivate social and ecologically just nature-culture relations grounded in Indigenous ways of knowing, being, and making. In this article we focus specifically on clay making and the ways in which onto-epistemic heterogeneity can be engaged to create transformative maker spaces. We present findings from an analysis of the pedagogies of walking, observing and talking lands and waters to outline principles of Indigenous making and sharing in youth-based learning environments.